Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve -2y+1=y-5

Y=6

Y=-6

Y=-2

Y=3


Sagot :

Answer:

y=2

Step-by-step explanation:

-2y+1=y-5

Add 2y to each side

-2y+2y+1=y+2y-5

1 = 3y -5

Add 5 to each side

1+5 = 3y-5+5

6 = 3y

Divide each side by 3

6/3 = 3y/3

2 =y

Answer:

y=2

Step-by-step explanation:

Move y to the other side by subtracting by y on both sides:

-y-2y+1=y-y-5

-3y+1=-5

Move the 1 to the other side by subtracting by 1 on both sides:

-3y+1-1=-5-1

-3y=-6

Divide -3 on both sides to eliminate the -3 on y

-3y/-3=-6/-3

y=2

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.